Quantitative 3D characterisation of porous NiTi fabricated by self-propagating high temperature synthesis using X-ray microtomography. (March 2015) - Gupta, C.; van de Casteele, E.; Wevers, M.; Hoshino, H.; Kobayashi, M.; Biswas, A.
<x content-type="archive" xml:space="preserve">Abstract</x> A porous NiTi specimen prepared by self-propagating high temperature synthesis for bone implant applications has been characterised by a laboratory X-ray microtomography instrument to reveal the three-dimensional (3D) structure of the internal porosity. The reconstructed slices obtained from the tomography scan showed open porosity as well as micropores in the matrix. The 3D renderings revealed that the open porosity is highly interconnected, tortuous structure. 3D quantitative estimates of the micropores in terms of their volume fraction, number density and size have been evaluated. Metrics have been developed based on skeletonised idealisation of the complex architecture of interconnected pores that reflect its structural properties.